When we add 4 to each side of the equation, we are applying the addition property of equality:
![a=b\Rightarrow a+c=b+c](https://img.qammunity.org/2023/formulas/mathematics/college/iieqg2r7mhmc4n4khvvhdmg6uefo9tk4ns.png)
We can prove this by solving the orginal equation for b, and then solving it again after adding 4 to each side:
Original:
![\begin{gathered} 10b+18=38 \\ 10b=38-18 \\ 10b=20 \\ b=(20)/(10) \\ b=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yy4fc1nz3wc7uc29xqlvc529hjuvyl1nsg.png)
After addition:
![\begin{gathered} 10b+18+4=38+4 \\ 10b+22=42 \\ 10b=42-22 \\ 10b=20 \\ b=(20)/(10) \\ b=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bl04n7rz88mpr55b0agdzstu3k1jb3mh0q.png)
The result is the same for both, confirming what the addition property tells.